A clinical audit on longer-term stroke management as a specific service in a primary care setting: Assessing adherence of service and clinical parameters. - Gadaffi Mostapha; Noor Azah Abd Aziz; Mohd Fairuz Ali (PLOS Global Public Health)
Primary-care long-term stroke care service offers comprehensive management at the community level. A clinical audit was carried out to assess the services of this clinic as compared to the established standardized criteria for longer-term stroke care.A retrospective audit was performed to evaluate the adherence to service parameters based on eleven criteria adapted from the Canadian Post-Stroke Checklist. The following clinical parameters were audited using the Malaysian CPG on Cardiovascular Disease 2017 and Malaysian CPG on Ischemic Stroke 2020: systolic blood pressure (SBP), diastolic blood pressure (DBP), low-density lipoprotein cholesterol (LDL-C), HbA1c, and weight, and smoking status. 113 registered patients from the 2022 clinic census were audited using paired Student's t-test and McNemar's test.Overall, only 2 out of 11 criteria for service parameters did not meet the standard: inquiring about patient fatigue (43.4%) and access to community resources (26.5%). The attainment of the target for BP and HbA1c meets the standards set for this audit. Patients experienced reduced SBP, DBP, LDL-C, and HbA1c levels, and a statistically significant reduction was observed in DBP (4.15 mmHg, p<0.05) and LDL-C (0.30 mmol/L, p<0.05). A notable reduction in the percentage of smokers (p<0.05) was also seen.Post-stroke patients at a specific-service clinic within the primary care setting benefited from clinicians' high adherence to clinical guidelines, observed from improved clinical parameters. These may serve as an impetus for clinicians to include long-term stroke service as a specialized service within primary care specialties.